The rugby tug-of-war: Exploring concussion-related behavioural intentions and behaviours in youth community rugby union in New Zealand. Issue 4 (August 2022) - Salmon, Danielle M; Badenhorst, Marelise; Walters, Simon; Clacy, Amanda; Chua, Jason; Register-Mihalik, Johna; Romanchuk, Janelle; Kerr, Zachary Y; Keung, Sierra; Sullivan, S. John; Whatman, Chris
Rugby union is a popular team sport, with a high rate of concussions. In adolescents, concussions are further complicated by issues of under-reporting. To encourage more responsible concussion behaviours, it is imperative to understand the factors that influence youth players' behaviours, including the attitudes and behaviours of their coaches and parents. The aim of this study was to explore concussion-related behavioural intentions and behaviours that may influence effective concussion management across a youth rugby system. The study adopted a pragmatic, descriptive qualitative design and included high schools from four youth rugby catchment areas in New Zealand. Nineteen focus groups and 2 individual interviews were conducted with n = 75 players, n = 22 parents, and n = 8 coaches (N = 105) during the 2018 rugby season. A thematic analysis was conducted, guided by a system's approach and the Theory of Planned Behaviour. The themes generated reflected a 'tug-of war' between various behavioural intentions and reported behaviours present in a youth rugby system. Additionally, the behavioural intentions and reported behaviours of coaches, parents, players and their teammates are intricately linked and collectively influence effective concussion management. Being aware of concussions and caring about their management and consequences was a strong theme present across the system. However, these favourable attitudes and behaviours were countered by players, parents and coaches disregarding the system, downplaying the seriousness of concussion, being competitive and driven to win, regardless of the risks. In players the warrior mentality theme, which included bravado, being tough, and playing through the pain further complicated effective concussion management. The findings suggest that there is not always a strong, favourable network in place that would facilitate similarly favourable concussion-related behaviours. To effect change, a system-wide approach, that takes the unique needs of each stakeholder into account and ultimately aims to reconcile performance and brotherhood with positive concussion related behaviours, is needed.